2019
DOI: 10.1111/are.14372
|View full text |Cite
|
Sign up to set email alerts
|

Expression analyses of digestive enzymes during early development and in adults of the chame fishDormitator latifrons

Abstract: This study describes the expression of genes that encode digestive enzymes (trypsin, pepsinogen, maltase-glucoamylase, sucrase-isomaltase, alkaline phosphatase and leucine aminopeptidase) using qRT-PCR in 0-to 7-day post-hatching (dph) chame (Dormitator latifrons). Additionally, adults liver and intestine were analysed for enzyme expression.Results showed that transcripts for all enzymes are present in both adult and larvae tissues. In adults, the expression of maltase-glucoamylase and sucrose-isomaltase showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…Almost digestive enzyme genes expression (excepted amy and pep) were detected at hatching, it's concurrent with the digestive enzyme activities. The expression of try in S. chuatsi larvae were detected at hatching and stained slight fluctuations until 15 dph, these results agree with other reports in larvae of several fish species [1,11,26] . Then, the expression of try gradually decreased until 30 dph, similar findings about try expression have been reported in other species such as Lates calcarifer [3] , Clarias magur [8] , Lutjanus guttatus [27] and…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Almost digestive enzyme genes expression (excepted amy and pep) were detected at hatching, it's concurrent with the digestive enzyme activities. The expression of try in S. chuatsi larvae were detected at hatching and stained slight fluctuations until 15 dph, these results agree with other reports in larvae of several fish species [1,11,26] . Then, the expression of try gradually decreased until 30 dph, similar findings about try expression have been reported in other species such as Lates calcarifer [3] , Clarias magur [8] , Lutjanus guttatus [27] and…”
Section: Discussionsupporting
confidence: 92%
“…showed that the expression of alp gene was detected at hatching, but it remained a very low level until 10 dph. Similar pattern has been observed in Dormitator latifrons [11] , the expression of alp was not high at early stage. This might be related to the development of the gut of fish, as well as other genes involved in the development of the digestive tract such as leucine aminopeptidase (lap).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Data are the mean ± activity was found in early and late pre-juveniles. This suggests that this activity could correspond to a sucrase-independent maltaseglucoamylase complex (Bertucci et al, 2019;Brun et al, 2020;Chaudet et al, 2019;Dhital et al, 2013;Morelos-Castro et al, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…However, the functions and capabilities of fish stomachs have changed (they have even been lost in some species) as fish evolved (Castro et al 2014). As is the case of some species of the sleeper family, such as D. latifrons, which, according to some reports, lacks a true stomach and has detritivorous (Morelos-Castro et al 2019) and omnivorous habits too (Freire-Lascano 2016). In general, the study of the passage of food through the digestive tract of fish suggests that, in addition to the specific anatomical-physiological characteristics of each species, there are factors that influence the transit time of food, such as culture temperature, stress, intestinal size and length, body size, hardness and composition of diets (Logothetis et al 2001, Booth et al 2008, Uscanga et al 2010, Andersen 2012, Khan & Seyhan 2019.…”
Section: Introductionmentioning
confidence: 99%